SLANG WORDS USED IN NOVEL “HARRY POTTER AND THE CHAMBER OF SECRETS” BY J.K. ROWLING - Zulindra, Ryan Achmad Kusuma; Apriyanti, Fitri; Buansari, Istihayyu (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
The purpose of this research was to identify the different types of slang words and their meanings. Slang is an informal word that is often used by a certain group of people and usually differs in each region, so it is necessary to be researched to enjoy reading novel from a foreign country. The data was analyzed by reading the whole novel and looking for phrases that reflected slang words. The method used in this research was qualitative textual analysis and theories from experts. The theories used in this research were based on (Leech, 1974) seven types of slang word meaning: conceptual, connotative meaning, stylistic meaning, affective meaning, reflected meaning, collocative meaning, and thematic meaning, as well as (Connie C. Elbe, 1996) examines that slang is an ever-changing set of colloquial words and phrases that speaker use to establish or reinforce a social identity of cohesiveness within a group or with a trend or fashion in society at large. The result of the research showed that there are sixty eights slang expressions were examined, and the slang words meanings discovered in this research were mostly expressed by their denotative meanings.